Protective Effect of the HIF-1A Pro582Ser Polymorphism on Severe Diabetic Retinopathy - Neda Rajamand Ekberg; Sofie Eliasson; Young Wen Li; Xiaowei Zheng; Katerina Chatzidionysiou; Henrik Falhammar; Harvest F. Gu; Sergiu-Bogdan Catrina (Journal of Diabetes Research)
Objective. Hypoxia is central in the pathogenesis of diabetic retinopathy (DR). Hypoxia-inducible factor-1 (HIF-1) is the key mediator in cellular oxygen homeostasis that facilitates the adaptation to hypoxia. HIF-1 is repressed by hyperglycemia contributing by this to the development of complications in diabetes. Recent work has shown that the HIF-1A Pro582Ser polymorphism is more resistant to hyperglycemia-mediated repression, thus protecting against the development of diabetic nephropathy. In this study, we have investigated the effect of the HIF-1A Pro582Ser polymorphism on the development of DR and further dissected the mechanisms by which the polymorphism confers a relative resistance to the repressive effect of hyperglycemia. Research Design and Method. 703 patients with type 1 diabetes mellitus from one endocrine department were included in the study. The degree of retinopathy was correlated to the HIF-1A Pro582Ser polymorphism. The effect of glucose on a stable HIF-1A construct with a Pro582Ser mutation was evaluated in vitro. Results. We identified a protective effect of HIF-1A Pro582Ser against developing severe DR with a risk reduction of 95%, even when adjusting for known risk factors for DR such as diabetes duration, hyperglycemia, and hypertension. The Pro582Ser mutation does not cancel the destabilizing effect of glucose but is followed by an increased transactivation activity even in high glucose concentrations. Conclusion. The HIF-1A genetic polymorphism has a protective effect on the development of severe DR. Moreover, the relative resistance of the HIF-1A Pro582Ser polymorphism to the repressive effect of hyperglycemia is due to the transactivation activity rather than the protein stability of HIF-1α.